Amplifying Peace Education Through Ethno-STEM Learning to Improve Students' Religious Moderation and Science Literacy - Anggraini, Putri Intan; Nurhapiza, Nurhapiza; Rahayu, Yuni; Ilhami, Aldeva (Journal of Indonesian Science Teachers, 2025)
Tolerance is the key to peace created from competent resources as an implication of quality education in accordance with the goals of the SDGs. The implementation of peace education can be applied through learning innovations through strengthening character education based on local wisdom. This research is motivated by the lack of innovation in local wisdom-based science learning (Ethno-STEM). The purpose of the study was to test the effectiveness of STEM model learning with an ethnoscience approach (Ethno-STEM). This type of research is a quasi-experiment with the research design used, namely nonequivalent control group designs. The instruments used were questionnaires in the form of a Likert scale referring to the Kemenag framework and science literacy tests referring to the PISA 2018 framework. Sampling was carried out using the cluster random sampling method and analyzed statistically inferentially using SPSS 22 software. The results of the study showed a positive response to strengthening religious moderation and science literacy of Madrasah Tsanawiyah students through STEM model learning with an ethnoscience approach. Based on the Mann Whitney test, with p. value 0.00 < 0.05, indicating a significant difference in scientific literacy and religious moderation in the class given the treatment. While in scientific literacy, students in the control class scored 65% and students in the experimental class scored 73.4%. It can be concluded that the STEM model with an ethnoscience approach can influence religious moderation and scientific literacy. and also strengthening peace education.